Programa de entrenamiento de los fundamentos técnicos del futbol en el pase en niños de 8 a 12 años de la Liga Cantonal de Buena Fé - Montes Ayala, Joel Antonio (2023)
The present work is focused on a case study that will pay special attention to the training program of children from 8 to 12 years old of the Buena Fe Cantonal League to learn the technical fundamentals of soccer specifically in passing. To do this, it will be necessary to investigate how they develop this training program, so opinions will be taken from the coaches as well as the children. and to measure its effect on technical performance during the training phase, an aspect adapted to the development of the research process to understand the conflicts that arise between the subjects of the training categories of this study. For this purpose, the aim is to evaluate the TRAINING PROGRAM OF THE TECHNICAL FUNDAMENTALS OF FOOTBALL IN THE PASS IN CHILDREN AGED 8 TO 12 OF THE CANTONAL LEAGUE OF BUENA FÉ to strengthen their skills and improve the physical and sporting performance of this town.